Shear strength variation of tailings material due to meteorological causes and its influence on the physical stability of tailings dam No. 3 Mahr Túnel - Mendoza Maldonado, Fernando (2019)
Meteorological conditions can produce alterations in the physical and chemical composition of materials stored in a tailings dam, as they modify their properties and the dam’s slope stability conditions. In this study, the shear strength behavior of tailings, as a result of meteorological causes, and its influence on the slope stability of tailings dam No. 3 Mahr Túnel, was assessed. To this end, consolidated undrained (CU) triaxial tests were conducted on undisturbed samples retrieved from the dam for different periods of weather exposure. The results show that tailings shear strength increases as the weather exposure period increases, which in turn enhance the factors of safety of the tailings dam stability analysis.